An investigation of the neural mechanisms of interval timing behaviour - Valencia Torres, Lourdes (2012)
Timing behaviour plays an important role in the daily living of individuals from a great variety of species. For example, organisms must be able to discriminate between the durations of relevant events (temporal discrimination) and to regulate their own behaviour in time (temporal differentiation). The processes that allow animals to adjust their behaviour to the temporal regularities of the environment have been studied using different procedures which model the relationship between time and behaviour. A taxonomy of timing based on the subject’s location in time with respect to the signalled duration has been proposed. When an organism judges the duration of an elapsed interval the timing is retrospective (e.g. interval bisection); when it responds during an elapsing duration the timing is immediate (e.g. fixed-interval peak procedure); and finally when it chooses between future delayed outcomes the timing is prospective (e.g. inter-temporal choice schedules). It has been proposed that the cortico-striato-thalamo-cortical (CSTC) circuits play a special role in interval timing and inter-temporal choice behaviour. This thesis examined whether performance of timing tasks by rats induces neuronal activation within the prefrontal cortex and corpus striatum, as revealed by Fos expression, and explored a new approach to analyzing performance in an inter-temporal choice schedule.